von Willebrand Factor Propeptide: A Potential Disease Biomarker Not Affected by ABO Blood Groups - Marianor, Mahat (Biomark Insights, 2015)
Epidemiological studies have shown that vascular-related disorders are associated with high von Willebrand factor antigen (VWF:Ag) and VWF propeptide (VWFpp). VWFpp is secreted together with VWF:Ag upon endothelial cell activation, hence it could be a potential biomarker. This study was conducted to compare between VWF:Ag and VWFpp levels among 30 healthy individuals and 42 patients with high levels of VWF:Ag in different medical conditions and ABO blood groups. VWFpp levels were strongly correlated with VWF:Ag. VWF:Ag and VWFpp levels were significantly increased in patients compared to healthy individuals. VWFpp is not affected by ABO blood group in both healthy individual and patient groups unlike VWF:Ag. As expected, this study showed that VWFpp levels increased in parallel with VWF:Ag levels in patients with diseases associated with endothelial activation. VWFpp though nonspecific is a potential biomarker reflecting underlying pathophysiological changes in various medical conditions with an additional advantage of not being influenced by ABO blood groups.